2020
DOI: 10.1080/19491034.2020.1806661
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the nuclear envelope with chromatin in physiology and pathology

Abstract: The nuclear envelope compartmentalizes chromatin in eukaryotic cells. The main nuclear envelope components are lamins that associate with a panoply of factors, including the LEM domain proteins. The nuclear envelope of mammalian cells opens up during cell division. It is reassembled and associated with chromatin at the end of mitosis when telomeres tether to the nuclear periphery. Lamins, LEM domain proteins, and DNA binding factors, as BAF, contribute to the reorganization of chromatin. In this context, an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 168 publications
0
18
1
Order By: Relevance
“…Plentiful other ANKLE2-host protein interactions have been found in large proteomic screens (59)(60)(61)(62). Presumably the bulk of these interactions are mediated through its ANK domain, which facilitates scaffolding functions in many proteins (63,64), or by the LEM domain, which is known to mediate interaction with the inner nuclear membrane lamina and BANF1 (65)(66)(67). It is particularly appealing to speculate that ZIKV leverages the protein interaction/scaffolding function of ANKLE2 to facilitate protein interactions within replication compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Plentiful other ANKLE2-host protein interactions have been found in large proteomic screens (59)(60)(61)(62). Presumably the bulk of these interactions are mediated through its ANK domain, which facilitates scaffolding functions in many proteins (63,64), or by the LEM domain, which is known to mediate interaction with the inner nuclear membrane lamina and BANF1 (65)(66)(67). It is particularly appealing to speculate that ZIKV leverages the protein interaction/scaffolding function of ANKLE2 to facilitate protein interactions within replication compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Large multiprotein structures, the nuclear pore complexes, span the nuclear envelope. Just interior to the INM is the nuclear lamina, a dense protein meshwork consisting of lamins and associated proteins that plays key roles in tethering heterochromatin to the nuclear periphery [18,19]. The ONM is continuous with the endoplasmic reticulum (ER) and retains many proteins in common with the ER [20,21].…”
Section: Nuclear Structure 21 the Nuclear Envelopementioning
confidence: 99%
“…The INM is known to contain >60 proteins, only some of which are characterized [16,21]. One important group of INM proteins is the LEM family, which contain the LAP2-Emerin-MAN1 (LEM) domain, a region that binds to the Barrier to Autointegration Factor (BANF1) (Figure 1) [18,21,29]. Mammals have seven genes encoding LEM proteins, including Emerin, LAP2 (gene name TMPO, encodes multiple splice forms including LAP2α and LAP2β), MAN1, LEMD1, LEMD2, ANKLE1, and ANKLE2 [30][31][32][33][34].…”
Section: Nuclear Structure 21 the Nuclear Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…Beneath the inner nuclear membrane, the nuclear lamina meshwork structure is formed to give the nucleus strength and elasticity ( 2 ). The nuclear lamina is composed of intermediate filaments (Lamin A, B or C) ( 3 ). It has been reported that nuclear shape abnormalities are more frequently observed in mouse embryonic fibroblasts featuring Lamin A deletion than those featuring deletion of Lamin B or C ( 4 ).…”
Section: Introductionmentioning
confidence: 99%